Teaching Patient Safety via a Structured Review of Medical Errors: A Novel Approach to Educating Residents About Medical Error, Disclosure, and Malpractice - Ethan Cumbler; Jeffrey Glasheen (Association of American Medical Colleges, 2007)
Abstract As the culture of medicine changes to reflect growing alarm about medical error, educating the next generation of physicians on the elements of patient safety provides a challenge for residency programs. This resource is a four-module comprehensive approach for internal medicine residents on medical error education, covering systems pressures, latent flaws, and psychological tendencies that predispose individuals to mistakes. This is paired with instruction on disclosure of and appropriate response to medical error. The program combines each didactic subject with interactive case-based analysis of adverse events using a novel structured form to guide discussion. In order to truly engage participants in patient safety, the learning paradigm needs to be one of active participation in projects that lead to meaningful change, not just of understanding and individual behavior but also in the underlying system of providing care. Based on the results of the pre- and postcurriculum survey and test, this program was able to increase resident understanding of the facts of medical error and change physician attitudes about contributions and response to error. After the curriculum, 91% of residents reported being more likely to disclose medical error to patients, and 72% reported interest in pursuing quality improvement projects. This pilot program demonstrates an effective structure for teaching patient safety and provides a response to the imperative that we in medicine take steps to change our ways of thinking about error.